Contrastive Study of Passive, Potential and Related Constructions in the Voice System:Early Middle Japanese and Contemporary Spanish - Shiba, Ayako (GENGO KENKYU (Journal of the Linguistic Society of Japan), 2020)
A common feature can be found in the voice system of Early Middle Japanese (EMJ) and Contemporary Spanish (the middle voice with se constructions). Both languages developed the passive and the potential constructions from the spontaneous (unaccusative) construction that expresses that a change occurs without an agent. They extend this spontaneous construal to the “agent-essential” verbs that express an event that requires the action of an agent.There is also a difference between the two languages, however. EMJ extended the spontaneous construal with the speaker’s point of view and mainly developed the animate-subject passive and the realization construction, which is called the non-volitional or potential use in previous studies. Uses of inanimate-subject passives were not as common in EMJ as they are in contemporary European languages, because it developed the realization construction where the inanimate-subject passives would be used in European languages.In contrast, Spanish extended the spontaneous construal to the “agent-essential” verbs in a neutral point of view and mainly developed the inanimate-subject passive and impersonal constructions. In a very limited condition, the Spanish middle voice has a potential meaning. Furthermore there are seldom animate-subject passives because it has a reflexive construction in the range where the EMJ developed animate-subject passives.